Proinflammatory mediators, TNFα, IFNγ, and thrombin, directly induce lymphatic capillary tube regression - Kemp, Scott S.; Penn, Marlena R.; Koller, Gretchen M.; Griffin, Courtney T.; Davis, George E. (Frontiers in Cell and Developmental Biology, 2022)
In this work, we sought to investigate the direct effects of proinflammatory mediators on lymphatic endothelial cell (LEC) capillaries and whether they might induce regression. Our laboratory has developed novel in-vitro, serum-free, lymphatic tubulogenesis assay models whereby human LEC tube networks readily form in either three-dimensional collagen or fibrin matrices. These systems were initially conceptualized in the hopes of better understanding the influence of proinflammatory mediators on LEC capillaries. In this work, we have screened and identified proinflammatory mediators that cause regression of LEC tube networks, the most potent of which is TNFα (tumor necrosis factor alpha), followed by IFNγ (interferon gamma) and thrombin. When these mediators were combined, even greater and more rapid lymphatic capillary regression occurred. Surprisingly, IL-1β (interleukin-1 beta), one of the most potent and pathologic cytokines known, had no regressive effect on these tube networks. Finally, we identified new pharmacological drug combinations capable of rescuing LEC capillaries from regression in response to the potent combination of TNFα, IFNγ, and thrombin. We speculate that protecting lymphatic capillaries from regression may be an important step toward mitigating a wide variety of acute and chronic disease states, as lymphatics are believed to clear both proinflammatory cells and mediators from inflamed and damaged tissue beds. Overall, these studies identify key proinflammatory mediators, including TNFα, IFNγ, and thrombin, that induce regression of LEC tube networks, as well as identify potential therapeutic agents to diminish LEC capillary regression responses.